E-waste recycling in an optimized way for copper recovery by leaching and a case study on E-waste generation and management in Dhaka city - Kaniz Fatema; Md Niamul Hassan; Sanjida Hasan; Hridoy Roy (Heliyon)
The widespread adoption of electronic devices has enhanced living standards but has also led to a surge in electronic waste (e-waste), creating serious environmental and health challenges. Although various methods exist to recover valuable metals from e-waste, each has notable drawbacks. Among these, chemical leaching with aqua regia is widely used but is both highly corrosive and hazardous. This study introduces a safer, more environmentally friendly approach to copper recovery from e-waste using an iron-based leaching solution. A combination of experimental procedures and computational modeling was employed to optimize copper extraction from printed circuit boards (PCBs). The experiments involved treating PCBs with iron-based solutions of different concentrations and testing the effectiveness over two distinct time periods. The most effective recovery rate, 72.69 % over five days, was achieved using a 50:50 mixture of ferrous and ferric sulfate. Computational analysis with Python's SciPy library further identified 5.92 g of PCB as the ideal input quantity for the process. In addition to the lab-based work, a survey of Dhaka's primary e-waste recycling hubs, Nimtoli and Elephant Road, revealed that approximately 1173 tons of e-waste are processed in these areas each year. Based on experimental findings, the survey findings have a projection to generate over 35 million BDT annually through copper recovery. However, despite government initiatives to regulate e-waste management, unsafe handling practices remain widespread. These practices not only endanger workers and the environment but also hinder regulatory efforts. The study emphasizes the urgent need for stricter regulations, greater public awareness, and the adoption of eco-friendly methods, like the proposed iron-based solution, to ensure safer and more effective copper recovery.